2014
DOI: 10.17795/compreped-25049
|View full text |Cite
|
Sign up to set email alerts
|

Non-traumatic Coma in Children in South-East of Iran

Abstract: Background: Non-traumatic coma is a common condition in children that may cause considerable morbidity and mortality. Determining the most common causes of loss of consciousness in any specific region, and any sex and age group will dramatically reduce mortality and morbidity. Objectives: The purpose of this study was to evaluate the most common causes of non-traumatic coma among children in south east of Iran. Patients and Methods: All children (aged 1 month to 15 years) hospitalized for non-traumatic coma we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…But regarding age groups in relation to etiology, neuroinfection was most common in the 1 month to 1 year age group. A study from Iran found infectious encephalopathy most commonly in children < 2 years; whereas toxic coma was significantly more frequent in the -6 year age group [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But regarding age groups in relation to etiology, neuroinfection was most common in the 1 month to 1 year age group. A study from Iran found infectious encephalopathy most commonly in children < 2 years; whereas toxic coma was significantly more frequent in the -6 year age group [20].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the second most common etiology of NTC was toxic-metabolic causes. A study from Iran that included 123 children reported the most common cause of NTC as toxic encephalopathy (followed by infectious encephalopathy) [20]. In a series from Nigeria, epileptic encephalopathy was reported as the second most common cause of NTC [24].…”
Section: Discussionmentioning
confidence: 99%
“…This also emphasizes the challenges considered in an association of status epilepticus with the outcome due to potential confounding factors such as the underlying etiology of status epilepticus and heterogeneity of studies in terms of study design, study populations, and outcome measures [23,27]. Nonetheless, it should be noted that there is a considerable geographic difference in prevalent etiologies of NTC across the world and being familiar with the common causes of NTC coma in the specific geographical region is considered to be important for physicians to implement accurate diagnostic and therapeutic measures [21].…”
Section: Discussionmentioning
confidence: 99%
“…Infective pathologies are considered to be the most common cause of NTC in children in developing countries, while toxic-metabolic causes and HIE show higher prevalence in Western countries [3-5, 19, 20]. In addition, infectious etiology was also reported to be associated with higher mortality rates compared to other NCT etiology groups [3,4,6,8,9,20,21]. Our findings are in line with the high prevalence of infectious etiology in pediatric NTC cases, whereas do not support the associated high risk of mortality given the mortality rate of 5.9% in our patients NTC due to infectious etiology.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, monitoring the patients at the risk for decompensation based on coma scores enables a more complete assessment of their state of consciousness and better management from the moment they are admitted to the intensive care unit. 9 10 11 12…”
Section: Discussionmentioning
confidence: 99%